Genética del doblaje cinematográfico. La versión del traductor como proto-texto en el filme Rio - De los Reyes Lozano, Julio (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This paper analyses the Spanish dubbed version of the animated film ‘Rio’ from a genetic point of view. Dubbing is the audiovisual translation mode which consists in re-recording the original voice track in the target language: although involving a large group of professionals, the translator’s task is pivotal to this process as he or she is responsible for transferring the information from one language to another. However, the text produced by the translator is not what will be heard on screen, as it will go through some transformations and rewritings during the dubbing process. It might even be considered a work-in-progress text, since a closer look reveals a high presence of hesitations, comments and other remarks addressed to the next agents. Once detected and classified, these marks will help us describe the dialogic relationship among some of the professionals involved in the dubbing process.